Final Survival Outcomes With Ramucirumab Plus Erlotinib Versus Placebo Plus Erlotinib in Patients With Untreated EGFR-Mutated Metastatic NSCLC: RELAY Japanese Subset - Makoto Nishio, MD, PhD; Takashi Seto, MD, PhD; Martin Reck, PhD; Edward B. Garon, MD; Kazuto Nishio, MD, PhD; Kazuo Kasahara, MD, PhD; Kazumi Nishino, MD, PhD; Miyako Satouchi, MD, PhD; Kiyotaka Yoh, MD; Hidetoshi Hayashi, MD, PhD; Kazuko Sakai, PhD; Sotaro Enatsu, MD, PhD; et al. (JTO Clinical and Research Reports)
Introduction: Significant improvement in progression-free survival (PFS; primary end point) was reported in the phase 3 RELAY study with ramucirumab (RAM) plus erlotinib (ERL) versus placebo (PL) in untreated EGFR-mutated NSCLC (hazard ratio [HR] = 0.59, 95% confidence interval [CI]: 0.46–0.76, p < 0.0001), including in the Japanese subset. We report updated PFS and final overall survival (OS) for the Japanese subset. Methods: Patients (no central nervous system metastases) were randomized 1:1 (stratification included EGFR leucine to arginine substitution [L858R]/exon 19 deletion [ex19del]) to ERL (150 mg/d) with RAM (10 mg/kg; n = 106) or PL (n = 105) intravenously every 2 weeks. The study was not powered for OS. Results: At final OS data cutoff (median follow-up = 48.2 mo), PFS benefit was sustained with RAM plus ERL versus PL plus ERL (median [m] PFS: 19.4 versus 11.2 mo; HR = 0.69, 95% CI: 0.51–0.93); the mOS was 54.3 and 46.0 months (HR = 0.91, 95% CI: 0.65–1.26), respectively. In L858R (n = 110) and ex19del (n = 100) subgroups, the mOS was 54.3 versus 43.2 months (HR = 0.63, 95% CI: 0.40–0.99) and 53.9 versus 62.1 months (HR = 1.40, 95% CI: 0.86–2.28), respectively. T790M rates post-progression were 52.0% versus 51.1%, respectively. Osimertinib as subsequent therapy was received by 61.0% versus 55.2% patients (L858R: 58.2% versus 48.1%; ex19del: 65.3% versus 62.7%); the median (range) osimertinib treatment duration was 16.8 (0.7–58.3) versus 20.1 (2.1–77.2) months. Safety was consistent with known RAM and ERL profiles, with no increased toxicity over time. Conclusions: The Japanese subset reported that RAM plus ERL improved PFS, and a mOS greater than 50 months was achieved. OS differed by EGFR mutation type, with an indication of benefit for patients with L858R. Trial Registration: NCT02411448